2022
DOI: 10.1186/s12875-022-01889-3
|View full text |Cite
|
Sign up to set email alerts
|

Mode of treatments and achievement of treatment targets among type 2 diabetes patients with different comorbidities – a register-based retrospective cohort study in Finland

Abstract: Aims Type 2 diabetes (T2D) is a progressive disease often associated with comorbidities that complicate the management of T2D and affect the achievement of treatment targets. However, adherence to guidelines and individualized treatments can potentially improve treatment outcomes. This study assessed the association between different glucose lowering and lipid lowering medication lines and the achievement of treatment targets with different comorbidities among a T2D cohort in North Karelia, Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…Our findings on prescription of lipid-modifying drugs (statins) by SMI status align with the few previous studies that have investigated this [ 16 , 17 ]. A Danish study reported that having a hospital diagnosis of depression was associated with a greater likelihood of initiation of treatment with lipid-modifying drugs, but they did not stratify by history of CVD [ 17 ].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Our findings on prescription of lipid-modifying drugs (statins) by SMI status align with the few previous studies that have investigated this [ 16 , 17 ]. A Danish study reported that having a hospital diagnosis of depression was associated with a greater likelihood of initiation of treatment with lipid-modifying drugs, but they did not stratify by history of CVD [ 17 ].…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies on SMI and cardiovascular risk management in people with diabetes have focused on investigating lipid levels [ 12 18 ], BP [ 13 15 ] and/or glycaemic levels [ 12 , 14 18 ], as these key cardiovascular risk factors can be managed pharmacologically if lifestyle modification is ineffective [ 13 – 19 ]. The findings are contradictory, with some studies reporting no difference in risk factor levels [ 13 , 14 , 16 ] and others finding either better [ 17 ] or worse [ 12 ] lipid levels, better BP [ 15 ], and better [ 12 ] or worse [ 15 , 18 ] glycaemic management among those with SMI. In the UK, clinical guidelines indicate that lipid-modifying medication (statins) should be offered to all those with diabetes over 40 years of age, irrespective of cholesterol levels [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations